2017
DOI: 10.1007/s00348-017-2386-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of solid–fluid selection options for optical-based measurements in single-phase liquid, two-phase liquid–liquid and multiphase solid–liquid flows

Abstract: Experimental techniques based on optical measurement principles have experienced significant growth in recent decades. They are able to provide detailed information with high-spatiotemporal resolution on important scalar (e.g., temperature, concentration, and phase) and vector (e.g., velocity) fields in single-phase or multiphase flows, as well as interfacial characteristics in the latter, which has been instrumental to step-changes in our fundamental understanding of these flows, and the development and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 267 publications
(222 reference statements)
1
37
0
Order By: Relevance
“…Measurements in all three dimensions are also possible with volumetric illumination and more than one camera (Maas et al 1993;Kreizer and Liberzon 2011). A recent review by Wright et al (2017) demonstrates previous works conducted in matched refractive index systems.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements in all three dimensions are also possible with volumetric illumination and more than one camera (Maas et al 1993;Kreizer and Liberzon 2011). A recent review by Wright et al (2017) demonstrates previous works conducted in matched refractive index systems.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that hydrogel may be fractured into grains for the study of packed bed flows. Other RIM liquid-solid pairs have the solid material with the potential for seeding as reported in Budwig (1994), Wiederseiner et al (2011), andWright et al (2017). A likely candidate for solid seeding, in addition to the presently tested hydrogel, would be silicone rubber, which is paired with aqueous solution of sodium chloride and glycerol (Shuib et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These limitations become even more restrictive when PIV is coupled with RIM because both fluid and solid objects may become indistinguishable. In the RIM method, the refractive index of two transparent materials are matched such that light is not refracted or reflected at the interface between the materials making the solid disappear in the fluid (Budwig, 1994;Wiederseiner et al, 2011;Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a fully RI-matched system is desired to avoid such optical distortions ( Wright et al, 2017 ). However, this is a challenging task to accomplish for liquids and pipe materials with properties comparable to those encountered in actual practical applications.…”
Section: Optical Diagnostic Techniquesmentioning
confidence: 99%
“…The average uncertainty in the elevation difference at the horizontal configuration was estimated at ± 2.1 mm over the total pipe length. For the purpose of reducing optical distortions, the optical measurement location was located in the quartz pipe section, L / D = 209 from the inlet, since quartz matches the RI of the oil phase ( Wright et al, 2017 ).…”
Section: Flow Facility Apparatus and Test Fluidsmentioning
confidence: 99%